Chemistry Learning Media Innovation: Interactive Website Development for Buffer Solution Material - Fastaqima, Fina; Sundus, Maria (Journal of Chemical Learning Innovation, 2024)
Purpose of the study: To determine the feasibility of website-based buffer solution learning media as a learning resource for class XI students at State Senior High School 13 Semarang. Methodology: This study used the Research and Development method, with the Thiagarajan model, which includes defining, designing, and developing. The feasibility of the learning media was based on the assessment results of media experts, material experts, high school chemistry educators, and student responses to the website-based learning media. Main Findings: The assessment results from material experts were 66.67%, categorized as good. The assessment results from media experts were 86.1%, categorized as very good. The assessment results from high school chemistry educators were 79.1%, categorized as good. The results from the student response questionnaire were 76.67%, categorized as good. Based on these results, it can be concluded that website-based learning media is suitable for use as a learning resource for students. Novelty/Originality of this study: This study presents the development of a website-based chemistry learning medium specifically designed for the topic of buffer solutions, integrating interactive features and self-paced learning components. Unlike previous studies, this study emphasizes accessibility and conceptual understanding through a digital platform. This research advances existing knowledge by providing an innovative and validated learning resource that supports flexible learning and enhances student engagement and understanding in chemistry education.